Theory and practice of state administrative law - La Ode Faiki*; Muhammad Iqbal Azhari (Universitas Syiah Kuala, 2023)
According to the provisions of the law, not all actions of state administration officials must be against the law. The law that regulates the relationship between the state and citizens is state administrative law, also called civil law, and state administrative law is a set of norms that aim to create conditions so that state administrative institutions can carry out their functions, as well as function. time to protect citizens from the actions of state administrative agencies. State and protect the management of the State. himself, herself. Within the framework of administrative law, there are general principles of good governance which, if implemented in all aspects of governance, will make it impossible for a crisis in this country to occur. state administrative law: a) Means for the authorities to regulate and control society b) Regulate ways of citizen participation in the process of regulation and control. State Administrative Law also regulates state administrators who are divided into 3 forms of power as in the theory of Tripaja (Trias Politika), put forward by Montesqueiu, namely: (1) Legislative Power, namely the power to make regulations. (2) Executive power, namely the power to carry out regulations. (3) Judicial power, namely the power to try to defend regulations. Scope of State Administrative Law. Initially, many experts considered that state administrative law and state administrative law were one unit and could not be separated. State administrative law is only a special part of state administrative law. In short, state administrative law only has the same field as state constitutional law. However, what distinguishes state administrative law is seen as a special law, namely regulating or determining the limits of the authority of a government institution, while state administrative law is general law.